How mycobacteria take advantage of the weakness in human immune system in the modern world - Wen-Cheng Chao; Chia-Liang Yen; Chun-Hsin Wu; Chi-Chang Shieh (Journal of Microbiology, Immunology and Infection, 2020)
Tuberculosis (TB) infection remains a global health threat in recent decades partly due to a marked increase in the number of susceptible patients, including those with diabetes mellitus (DM) and who receive biologics. Immunity in TB infection is complex as Mycobacterium tuberculosis (MTB) is a highly adaptive pathogen and may evade the immune defense through various ways. Recent advances in TB immunity have revealed that granulomatous inflammation in TB infection is highly dynamic and the early influx of neutrophils may lead to excessive inflammation and pulmonary cavitation, which provide niches for MTB not only to survive but also to spread to other sites. Furthermore, reactive oxygen species have been found to play a crucial role among pathogenesis of TB infection in diabetics (DM-TB) through regulating inflammasome activation and the production of IL-1β, which in turn modulates the inflammatory network in TB infection, leading to dysfunctional inflammatory responses and tissue remodeling. To understand the exact immunological mechanisms underlying TB infection hence is essential for developing novel adjunctive host-directed therapy (HDT) aiming to alleviate excessive inflammation and tissue destruction and, at the same time, enhance the efficacy of currently available choices of anti-mycobacterial agents. Here we reviewed current epidemiological challenges of global TB control, novel immunological mechanisms underlying dysregulated inflammation in TB infection, especially in DM-TB, and some potential applications of adjunctive HDT in TB treatment. Keywords: Tuberculosis, Immunology, Diabetes, Biologics, Primary immunodeficiency disease, Host-directed therapy